Effects of repetitive transcranial magnetic stimulation with different frequencies on post-stroke aphasia: A PRISMA-compliant meta-analysis. Issue 24 (12th June 2020) - Li, Tiao; Zeng, Xiaoxiang; Lin, Lijuan; Xian, Tingting; Chen, Zhuoming
Abstract: Backgrounds: Previous studies indicated inconsistent results for the treatment effect of repetitive transcranial magnetic stimulation (rTMS) on post-stroke aphasics. The study conducted a meta-analysis to evaluate whether the rTMS with different frequencies demonstrated any effect in patients with post-stroke aphasia. Methods: Electronic databases (PubMed, Web of Science, Medline, EMBASE, and Google Scholar) were searched for articles published before July 2019. Statistical analyses were made using STATA 12.0 software. Standard mean difference (SMD) with 95% confidence intervals (CI) were calculated for the treatment effect of rTMS on post-stroke aphasia. Results: Meta-analysis indicated significant treatment effects on naming of rTMS in post-stroke aphasics (SMD 0.76, 95%CI 0.16 to 1.36, I 2  = 76.9%, P  < .001). Subgroup analyses showed significant treatment effects on naming of low frequency (LF)-rTMS (SMD 0.40, 95%CI 0.10 to 0.69, I 2  = 0.0%, P  = .671). However, the changes in repetition and comprehension following stimulation were not significant. Conclusions: In conclusion, we provide preliminary evidence that both LF-rTMS and high-frequency-rTMS might be relatively effective and safe treatment for post-stroke aphasics. However, LF-rTMS mainly plays a short-term role in subacute post-stroke aphasics. Longer-term and large-scale studies are essential to explore the effect of rTMS with different frequencies on post-stroke aphasia. Abstract : Supplemental Digital Content is available in the text